Rationality Of Analgesic-Antipyretic Use In Dengue Hemorrhagic Fever Patients - Indah Sri Hartini; Eko Yudha Prasetyo; Dyah Ayu Kusumaratni; Arshy Prodyanatasari (Sean Institute, 2023)
Dengue haemorrhagic fever (DHF) is a disease caused by acute dengue virus infection transmitted through the bite of the Aedes Aegepty mosquito. Data from the health department states that the increase in the Case Fatality Rate (CFR) of DHF in 2020 is 0.8% and in 2021 is 1.1% while the national target is <1%. DHF patients need proper treatment to minimize the occurrence of contraindications in patients. DHF patients generally experience initial symptoms of sudden high fever >38oC, headache or pain behind the eyeball, muscle and bone pain. Treatment of DHF patients to reduce the pain experienced is by giving the right antipyretic analgesic. Based on this, the researcher wants to examine the description of the use of analgesic-antipyretics to determine the rationality level of the use of analgesic-antipyretics in DHF patients. The rationality of analgesic-antipyretic use measured, including patient accuracy, drug accuracy, indication accuracy, and dose accuracy. The type of research conducted was non-experimental observational research with retrospective data collection and the sampling technique used was totality sampling. Data collection was carried out based on patient medical record data in the period January-August 2022. In accordance with WHO guidelines and the National Guidelines for Health Services for Dengue management, the provision of analgesic-antipyretic drugs in accordance with the drug of choice is paracetamol. Based on the data obtained, there were 74 DHF patients with 57% female patients and 43 male patients, and 42% of patients were children. The rationality of analgesic-antipyretic use in DHF patients is known to be 100% right patient; 37.84 right drug; 100% right indication; and 98.65% right dose.